EISYS Enrollment information system for the Technological Institute of the Philippines - Balanag, Geraldine C. (Animo Repository, 1992)
This information systems project was conducted for the Technological Institute of the Philippines. It is specifically addressed towards the incorporation of the attributes of an information system to the enrollment system of the school. The project codenamed, EISYS, which stands for Enrollment and Information System involves the integration of the different functions of the registrar and the accounting offices pertaining to student information and enrollment transaction processing. The inefficiencies of the current manual enrollment system of TIP brought about by the consistently increasing student population paved the way for the initiation of the EISYS project. Obviously, automation of the enrollment process is needed so as to cope up with the present and future needs of the academe. To justify the conversion from a fully manual system to automated, the proponents took the study a step further by extending the scope of the proposed system which now includes data banking (storage and retrieval) as well as a query and report generation facilities. The rationale behind this is that the utilization of computers would be further optimized and justified by incorporating information systems features than just confining automation to the level of transaction and data processing. In effect, EISYS involves two development areas. First is the development of a software which would provide for data banking and transaction processing features. Second is the modification of the present enrollment procedure so as to complement the EISYS software.